Impact of OVO Digital Wallet on Student Financial Management Behavior (Case Study in One of the Big Cities in Indonesia) - Anisah Firli; Nurul Fathiya (Budapest International Research and Critics University, 2022)
The high number of internet users in Medan City which reached 82,5% of the population in Medan City is one of the reasons why 70% of North Sumatra digital wallet users are in Medan City. Financial technology or fintech payment can influence a person’s managerial behavior because it creates a sense of security in making transactions. To address this, this study aims at analyzing the impact of OVO digital payment (one of Indonesia's most popular fintech payments) on university students’ financial management behavior. A total of 400 students in Medan City who use OVO digital wallet participated in this study. The sample size was determined using Slovin’s formulation and it was analyzed using simple linear regression. The hypothesis test was done by using a t-test. This study found that OVO has a significant impact on students' financial management behavior in Medan City. This study suggests that fintech payments should be used wisely to have a good impact on financial management behavior, particularly among students.